Bio-Nanohybrids Based on Layered Double Hydroxide - Choy, Jin-Ho; Park, Man; Oh, Jae-Min (Current Nanoscience, 2006)
Layered double hydroxides (LDHs) with high anion exchange capacity have attracted particular attention in the fields of bio-hybrid nanomaterials due to their unique properties such as excellent biocompatibility, high affinity to carbonate anion, pH-dependent stability and high availability. To date, a variety of negatively charged biomolecules have been hybridized with LDHs to evolve into bio-LDH nanohybrids, including vitamins, drugs and DNA strands as well as simple organic acids. Bio-LDH nanohybrids can be readily prepared in a mild condition by coprecipitation, anion exchange or reconstruction. Their applications can be found in a wide range from the controlled release and delivery systems to biosensors and genetic molecular code system. In this review, special emphasis has been placed on DNA-LDH nanohybrids because DNA molecules are of great importance in many sciences and industrial fields. Their synthesis methods, characteristics and application potentials are reviewed briefly.
Keywords: Bio-nanohybrids